Evaluation of Metro City Government Website Using WEBUSE Method - Ali Nasution; Dani Apriansyah; Netty Sefriyanti; M S Hasibuan (Proceeding International Conference on Information Technology and Business, 2021)
Metro City is one of the Madya Cities in Lampung Province which has the goal of